(untitled) (Applied Biological Research, 2023)
A study was designed to evaluate the spatial distribution of benthic macro-invertebrate communities in river Bhilangana, Uttarakhand (India). The samples were collected during March 2018 to February 2019 at five stations (S1 to S5) from headwater to mouth. The total mean density of benthic macro-invertebrate community varied significantly among the stations. Taxonomic composition revealed that Diptera as the most abundant taxa at S1 (3.6%), S2 (44.1%) and S5 (36.2%), and Trichoptera at S3 (30.5%) and S4 (34%). However, at family level, Simulidae was most abundant at S1 (11.2%) and S3 (11.2%), and Chironomidae at S2 (21.2%) and S5 (12.8%). Similarly, Limnephilidae (21.8%) was the most abundant taxa at S4. The assemblage patterns varied longitudinally from S1 (Simulidae - Limnephilidae - Philopotamidae - Chironomidae) to S2 (Chironomidae - Simulidae), S3 (Simulidae - Philopotamidae), S4 (Limnephilidae - Simulidae) and S5 (Chironomidae - Simulidae). Ordination technique PCA identified characteristic taxa at S1 (Belostomatidae and Vellidae), S2 (Chironomidae, Tabanidae and Psephenidae), S3 (Glossosomatidae, Hydropsychidae, Psychomyiidae, Agrionidae, Blepharoceridae and Leptidae), S4 (Caenidae, Haliplidae, Dryopidae and Dixidae) and S5 (Tipulidae and Corydalidae). The variation in the characteristic taxa at these stations was primarily attributed to substrate heterogeneity and forest type patterns; conifer-oak rhododendron, oak-rhododendron, pine-oak, etc.